Phenotypic spectrum of the RBM10‐mediated intellectual disability and congenital malformation syndrome beyond classic TARP syndrome features. Issue 3 (5th January 2021) - Kumps, Candy; D'haenens, Erika; Vergult, Sarah; Leus, Jasmine; van Coster, Rudy; Jansen, Anna; Devriendt, Koen; Oostra, Anna; Vanakker, Olivier M.
Abstract: Pathogenic variants in the RBM10 gene cause a rare X‐linked disorder described as TARP (Talipes equinovarus, Atrial septal defect, Robin sequence, and Persistent left vena cava superior) syndrome. We report two novel patients with truncating RBM10 variants in view of the literature, presenting a total of 26 patients from 15 unrelated families. Our results illustrate the highly pleiotropic nature of RBM10 pathogenic variants, beyond the classic TARP syndrome features. Major clinical characteristics include severe developmental delay, failure to thrive, brain malformations, neurological symptoms, respiratory issues, and facial dysmorphism. Minor features are growth retardation, cardiac, gastrointestinal, limb, and skeletal abnormalities. Additional recurrent features include genital and renal abnormalities as well as hearing and visual impairment. Thus, RBM10 loss of function variants typically cause an intellectual disability and congenital malformation syndrome that requires assessment of multiple organ systems at diagnosis and for which provided clinical features might simplify diagnostic assessment. Furthermore, evidence for an RBM10‐related genotype–phenotype correlation is emerging, which can be important for prognosis. Abstract :